(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يناقش هذا البحث قضية, لعلها من أهم قضايا علم البحث الاقتصادي الاجتماعي في الوقت الراهن, خصوصا بالنسبة لبلدان العالم النامي. يركز هذا البحث على مناقشة دور الدولة عبر التاريخ, وتعاظم هذا الدور في عقود ما بعد الحرب العالمية الثانية, ثم يتعرض لخصوصية, وأنماط هذا الدور في بلدان العالم النامي. كما يتعرض لمناقشة آراء, وحجج المناهضين لدور الدولة في الحياة الاقتصادية، وكذلك آراء الداعين إلى ترسيخ هذا الدور من خلال إعادة تقويمه وإصلاحه. ونختم هذا البحث بعرض بعض المقترحات والاستنتاجات التي يمكن أن تصلح لأن تكون باباً للحوار والمناقشة حول هذا الموضوع. This study deals with an issue which is probably of great importance in current socio-economic research especially in developing countries. It focuses on analyzing the government role in economy through history, a role which has become greater after the second world war It also deals with the special nature and types of this role in the developing world. Moreover it addresses the issues raised by the opponents of the government role in economy as well as the one supporting the arguments through reconstruction and reform. The study concludes with a number of propositions and results that might open further discussion on the topic.